The literary reading: an invitation to unfold yourself - Ramos, Flávia Brocchetto (2017)
The article discusses possibilities of composing and reading of the story E um rinoceronte dobrado, by Hermes Bernardi Jr., with drawings by Guto Lins, aiming to realize how the poetic aspect is created in this text by the interaction of languages, and researching therefore how the reading process tends to concretize in contemporaneous times. Based on Candido (200), Paz (1982) and Huizinga (1999), the analytical study points to the inherent dialogue to the current cultural production directed to children, aiming to elucidate the concept of childhood and of child being which underlies the literary text selected by the School Library National Program (PNBE), in order to compose collections present in Brazilian public schools libraries. In line with modern times, in which the coexistence of multiple codes predominates, the study indicates that the poetic text for children has been constituted by more than one language and it understands reading as a dynamic action in which the young reader acts on the literary work.